2022
DOI: 10.3847/1538-4357/ac35ca
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian Process Classification for Galaxy Blend Identification in LSST

Abstract: A significant fraction of observed galaxies in the Rubin Observatory Legacy Survey of Space and Time (LSST) will overlap at least one other galaxy along the same line of sight, in a so-called “blend.” The current standard method of assessing blend likelihood in LSST images relies on counting up the number of intensity peaks in the smoothed image of a blend candidate, but the reliability of this procedure has not yet been comprehensively studied. Here we construct a realistic distribution of blended and unblend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A compelling variant of GANs is also introduced and tested on nearby SDSS galaxies by Reiman & Gohre (2019), where they have the generator output two cutouts given one composite input cutout and fine-tune it by giving these two deblended cutouts as well as the two that were used to construct the composite to the discriminator. While in this work we improved the resolution/noise/pixel scale of ground-based images by training from the space data using GANs and performed source detection on the enhanced products using a standard peak-finding routine, Buchanan et al (2022) showed that detection of blends can be further improved using either Gaussian process or CNN-based blend classifiers. They also showed that the improvement in blend identification depends strongly on the footprint image they start with.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A compelling variant of GANs is also introduced and tested on nearby SDSS galaxies by Reiman & Gohre (2019), where they have the generator output two cutouts given one composite input cutout and fine-tune it by giving these two deblended cutouts as well as the two that were used to construct the composite to the discriminator. While in this work we improved the resolution/noise/pixel scale of ground-based images by training from the space data using GANs and performed source detection on the enhanced products using a standard peak-finding routine, Buchanan et al (2022) showed that detection of blends can be further improved using either Gaussian process or CNN-based blend classifiers. They also showed that the improvement in blend identification depends strongly on the footprint image they start with.…”
Section: Discussionmentioning
confidence: 99%
“…We simulated the blend sample from real galaxy cutouts, as opposed to using Galsim (Rowe et al 2015) models based on real galaxy distributions (e.g., Arcelin et al 2020;Buchanan et al 2022;Wang et al 2022) to be more representative of real galaxies. We restricted the training sample to galaxies brighter than the 24th magnitude in F750W, and in testing went down to 25th magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…A compelling variant of GANs is also introduced and tested on nearby SDSS galaxies by Reiman & Göhre 2019, where they have the generator output two cutouts given one composite input cutout and fine tune it by giving these two deblended cutouts as well as the two that were used to construct the composite to the discriminator. While in this work, we improved the resolution/noise/pixel scale of ground-based images by training from the space data using GANs and did source detection on the enhanced products using a standard peakfinding routine, Buchanan et al 2022 showed that detection of blends can be further improved using either Gaussian Process or CNN-based blend classifiers. They also showed that the improvement in blend identification depends strongly on the footprint image they start with.…”
Section: Discussionmentioning
confidence: 99%
“…We simulated the blend sample from real galaxy cutouts, as opposed to using Galsim (Rowe et al 2015) models based on real galaxy distributions (e.g., Arcelin et al 2020, Buchanan et al 2022, Wang et al 2022) to be more representative of real galaxies. We restricted the training sample to galaxies brighter than the 24th magnitude in F750W and in testing went down to 25th magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…A Gaussian process classifier was used for the classification, as research has shown its ability to predict well-calibrated probabilities and its superior performance compared to logistic regression [38]. Further, the Gaussian process classifier has been successfully used in medical studies [39,40].…”
Section: Feature Set and Modellingmentioning
confidence: 99%